Modeling of creep behaviour in Grade 91 steel under complex state of stress - Ferdous, I. U.; Nasrul Azuan, Alang; Juliawati, Alias; Asnul Hadi, Ahmad (Universiti Malaysia Pahang, 2025)
Power plant components such as boiler tubes, superheated pipes, and headers often operate under elevated temperatures, leading to creep failure. Due to their non-uniform geometries, these components experience complex states of stress. This study investigates the creep rupture characteristics of Grade 91 steel under multiaxial stress conditions, focusing on notched specimens with acuity ratios of 2.28 and 4.56. Creep rupture tests operated at 600°C revealed rupture lives ranging from 52 to 398 hours for the 2.28 acuity ratio and 81 to 890 hours for the 4.56 acuity ratio. Finite element analysis (FEA) incorporating a ductility exhaustion-based damage model predicted rupture lives within a ±2 scatter band of experimental results, demonstrating good agreement. The analysis also highlights those blunter notches show a shift in the locality of extreme damage from the notch root to the ligament center as creep progresses, while sharper notches exhibit localized damage near the notch root. Furthermore, the study establishes the transition between von Mises stress and maximum principal stress-controlled rupture mechanisms. The incorporation of skeletal stress into the Norton power law improved the accuracy of life predictions for non-uniform stress distributions.